Wetland vegetation of Biratnagar, Nepal - Niroula, Bhabindra; Jha, Sasinath (Nepalese Journal of Biosciences, 2015)
In total, 128 species of aquatic macrophytes (angiosperms 120, pteridophytes 6, bryophyte 1 and alga 1) were recorded among which 37 species were helophytes, 35 tenagophytes, 37 hyperhydates, 6 epihydates, 5 vittates, 1 rosulate and 5 pleustophytes on the basis of growth form. Based on the frequency of occurrence 2% were abundant, 12% frequent, 76% occasional and 10% scarce. Seven macrophyte communities were recorded on the basis of habitat. These were: 1. deep water submerged associes; 2. shallow water submerged associes; 3. Floating- leaf form associes; 4. free floating-leaf form associes; 5. Amphibious-marsh associes; 6. moist meadow associes; and 7. dry mud associes.